KETETAPAN MENGANALISIS REFORMASI KEBIJAKAN EKONOMI NASIONAL PROSPEK DAN TANTANGAN EKONOMI GLOBAL - Fitria Nilda; Syatria Hasni; Yustina; Elmasi Tri Oktaviani; Sumanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The trade war between the United States and China, along with the increasing trend of global economic fragmentation, has reshaped international trade, investment flows, and global supply chains. These developments have generated both challenges and opportunities for developing countries, including Indonesia, in maintaining economic competitiveness and attracting global investment. This study aims to analyze the impact of trade wars and global fragmentation on the Indonesian economy and to examine the economic policy reforms implemented in response to these changes. The study employs a qualitative method using a library research approach. Data were collected from scholarly articles, working papers, reports of international organizations, and policy documents published between 2021 and 2025. Data were analyzed through content analysis, involving the processes of identification, classification, interpretation, and synthesis of relevant literature. The findings indicate that trade wars and global economic fragmentation have affected Indonesia’s international trade performance, investment flows, and participation in global value chains. The restructuring of global supply chains has created opportunities for Indonesia to attract investment relocation and strengthen its domestic industrial sector. In response, the Indonesian government has implemented a range of economic reforms, including investment policy reforms, industrial downstreaming strategies, trade diversification, and efforts to enhance national economic resilience. These reforms are intended to increase domestic value added, strengthen economic competitiveness, and expand Indonesia’s integration into global economic networks. The effectiveness of these reforms depends on Indonesia’s ability to strengthen industrial capacity, improve human capital quality, and enhance linkages among investment, trade, and structural economic transformation.